2020
DOI: 10.7759/cureus.10174
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Patient Satisfaction in a Military and Public Hospital: A Comparative Study

Abstract: Background: In recent times, the assessment of patient satisfaction has become an essential tool for measuring the effectiveness of healthcare delivery. However, not a lot of work has been done in Pakistan, even less so in comparing it across different hospital systems in the country. This research aims to fill that gap and be the first to compare satisfaction levels in a military and public hospital. Objective: To assess patient satisfaction in different hospital systems of Pakistan and compare their outcomes. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 16 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…22 A study comparing patient satisfaction at two major hospitals in Lahore, revealed that patient satisfaction was significantly better (p=0.03) at one compared to the other. 23 A cross-sectional study interviewed 150 participants in the outpatient department of a hospital in Rawalpindi, and reported that overall satisfaction score was 61.4% 24 , while the current study had overall satisfaction rate of 68%.…”
Section: Discussionmentioning
confidence: 58%
“…22 A study comparing patient satisfaction at two major hospitals in Lahore, revealed that patient satisfaction was significantly better (p=0.03) at one compared to the other. 23 A cross-sectional study interviewed 150 participants in the outpatient department of a hospital in Rawalpindi, and reported that overall satisfaction score was 61.4% 24 , while the current study had overall satisfaction rate of 68%.…”
Section: Discussionmentioning
confidence: 58%
“…17 Farooq et al did a comparative analysis of PS in military and public sector hospitals in Pakistan and showed a deficiency in all seven dimensions of PS in public hospitals. 18 Naseer identified several determinants contributing to low PS in Pakistan, including the lack of privacy, limited autonomy, insufficient involvement in decision-making, poor communication and issues related to sanitation/hygiene. These factors were associated with negative patient experiences and were recognised as significant contributors to reduced satisfaction within the healthcare system.…”
Section: Discussionmentioning
confidence: 99%
“… 12 Similarly, another study conducted in Pakistan indicated a mean satisfaction score of 3.59 in the financial aspect. 18 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In major factors which affect patient satisfaction are waiting time, time spent with doctor, interpersonal communication, treatment outcome and services provided which are related to hospital. Minor factors which are usually non-modifiable include age, gender, educational status and health because patient satisfaction also variates according to gender, age, level of education and health status, but outcomes of these studies are conflicting 4,5 . Patients who are male and those whose age are older than 50, short spanned and fined health condition and education status at the primary level indicates a higher level of satisfaction6.…”
Section: Introductionmentioning
confidence: 99%